(untitled) (IIUC Business Review, 2022)
The study aims to examine the impact of religiosity, legal enforcement and good governance on tax evasion. The study utilizes a panel data of 7 SAARC countries covering the period of 2002 to 2015 and ordinary least square (OLS), fixed effect (FE) and random effect (RE) model have been applied as statistical technique to analyze the data. The results of the study show that (a) the religiosity has a negative impact on tax evasion, (b) enforcement level has been found positive in OLS and random effect but negative in fixed effect model, and (c) good governance in public sector has a negative impact on tax evasion. The results of the study are supposed to offer valuable insights to the researchers, tax practitioners and government for the development of an international tax framework, and implementing a sound policy. IIUC Business Review Vol. 7-8, Dec. 2018-19 pp. 61-88